(untitled) (Damascus University Journal of agriculture sciences, 2026)
The experiment was carried out in the farm field of the Faculty of Agriculture at Damascus University during the (2022/2023) agricultural season to study the effect of foliar spraying with zinc at concentrations (0.5-1-1.5 gł) and boron at concentrations (0.5-1-1.5 gł) on the growth of the local salmon onion plant and its production from seed. Spraying treatments (4 sprays) were applied at a rate of once every 20 days during the season, starting from the stage of 4-5 true leaves. The experiment was designed according to the complete randomized blocks, with four replicates per treatment and 15 plants epeat. The results showed that the combined double foliar spray treatment with both boron and zinc elements at concentration Zn1 + B1 gł was superior in vegetative growth indicators with significant differences on the untreated control, which was reflected positively in flowering and productivity indicators, as the combined treatment Zn1 + B1 gł achieved a significant increase in the percentage of flower setting, number of seeds, and plant seed yield (70.06%, 2800 seed, 40.50 g, respectively) compared with the untreated control (50.97%, 1996 seed, 28.12 g).